Using waste energy from the Organic Rankine Cycle cogeneration in the Portland cement industry (2015)
Cement production is intensive in terms of energy consumption. An analysis of the resources involved in manufacturing clinker needs a corresponding mass and energy balance. This balance may indicate the existence of residual heat flows that are not used. This paper summarizes the development of a protocol for the evaluation of a cement plant rotary kiln to implement an Organic Rankine Cycle (ORC) system for cogeneration. The results show that 19.2% of the energy preheater exhaust gas can be recovered to be used in producing 5.5 GWh/year of electricity and 23.7 GWh/year of thermal energy in the cement plant. The electricity generated would represent annual savings of 1.18 $/t cement. The thermal energy produced in cogeneration, equivalent to coal in the plant itself, represents cement savings of 0.51 $/t cement and emissions reductions of 8 kt CO2/year.